2014
DOI: 10.1016/j.intimp.2013.12.010
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activation of mouse neutrophils by recombinant human interferon-gamma: Increased phagocytosis and release of reactive oxygen species and pro-inflammatory cytokines

Abstract: Here, we investigated the ability of IFN-γ to modulate the functions of mouse neutrophils in vitro. Neutrophils incubated in the presence of IFN-γ showed enhanced phagocytosis in response to zymosan, opsonized zymosan or precipitated immune complexes of IgG and ovalbumin. The effect of IFN-γ was dose-dependent with an initial response at 10 U/ml and a maximal response at 150 U/ml; 2 h of incubation were required to reach the optimal response level. These stimuli can also induce IFN-γ-pretreated neutrophils to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 65 publications
1
37
0
8
Order By: Relevance
“…Interestingly, mice that received bi-specific T cell treatment had to be euthanized around the same time as control mice even though the tumor signals were dramatically lower (Figure 5). Our further studies indicated that there were highly elevated levels of human specific IFNγ and IL-6 in the mouse serum (Supplemental Figure S3) and it is probable that the mice died of cytokine release syndrome (25) rather than tumor. More interestingly, augmented anti-tumor efficacy induced by pp65 vaccine was supported in a relapsed tumor model (Supplemental Figure S4).…”
Section: Resultsmentioning
confidence: 92%
“…Interestingly, mice that received bi-specific T cell treatment had to be euthanized around the same time as control mice even though the tumor signals were dramatically lower (Figure 5). Our further studies indicated that there were highly elevated levels of human specific IFNγ and IL-6 in the mouse serum (Supplemental Figure S3) and it is probable that the mice died of cytokine release syndrome (25) rather than tumor. More interestingly, augmented anti-tumor efficacy induced by pp65 vaccine was supported in a relapsed tumor model (Supplemental Figure S4).…”
Section: Resultsmentioning
confidence: 92%
“…Immune activation has been shown to enhance phagocytosis and induce production of ROS, which play an important role in control of infection (41)(42)(43)(44)(45)(46)(47). Transcriptome analysis indicated that IFN-ε but not IFN-α induced the expression of genes involved in phagocytosis and ROS production ( Figure 6A).…”
Section: Ifn-ε Induces Ros That Protects Macrophages Against Infectionmentioning
confidence: 99%
“…IFN-γ has recently been produced by recombinant DNA techniques, providing a new opportunity to characterize the immunomodulatory properties this cytokine [4] . In our recent study titled "In vitro activation of mouse neutrophils by recombinant human interferon-gamma: increased phagocytosis and release of reactive oxygen species and pro-inflammatory cytokines" [5] , we investigate the ability of IFN-γ to modulated the functions of mouse neutrophils in vitro.…”
Section: Research Highlightmentioning
confidence: 99%
“…Our research group has being greatly interested in understanding the role of neutrophils in the interplay between the innate and acquired immune responses [5,7,8,9,10,11] , addressing the functional similarities and differences with macrophages. It has been suggested that during inflammation or specific immune responses, mature myeloid cells may respond to humoral factors in a manner analogous to macrophages [12] .…”
Section: Research Highlightmentioning
confidence: 99%